PENGARUH PERSEPSI MAHASISWA TENTANG INVESTASI TERHADAP MINAT BERINVESTASI SAHAM DI PASAR MODAL - Khristina Sri Prihatin (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2022)
This study aims to determine how students' perceptions of stock investment are, to find out how much students were interested in investing in stocks in the capital market, and to analyze how the perceptions of students majoring in Accounting Education at the University of Banten Jaya about investment affect interest in investing in stocks in the capital market. This study uses a quantitative research method consisting of two variables, namely student perceptions (X) and interest in investing (Y). The object of this research is students of Accounting Education, Faculty of Teacher Trainin g and Education, University of Banten Jaya. The source of the data used is primary data in the form of questionnaire results then tabulated and processed using SPSS 25.0 software with a series of tests and provisions that have been scientifically tested and secondary data includes documents and archives. Based on the results of the study, it was found that 40 respondents (53.3%) had a positive perception of stock investment, and 42 respondents (56%) had a high level of interest in investing in stocks in the capital market. The Influence of Student Perceptions About Investments on Interest in Investing in Stocks in the Capital Market (4.254>1.996) tcount> ttable, as much as 19.9% interest in investing in stocks is influenced by student perceptions of investment, the remaining 80.1% is influenced by other variables that are not included in this research.